Ivy + Bean break the fossil record - Barrows, Annie; Blackall, Sophie (San Francisco : Chronicle Books, 2007)
Everyone in second grade seems set on breaking a world record and friends Ivy and Bean are no exception, deciding to become the youngest people ever to discover a dinosaur skeleton.
School Library Journal, July 2007.
Booklist, July 2007.
Horn Book, April 2008.
Kirkus Review, June 2007.
3.1
K-3
Keywords: World records -- Juvenile fiction; Fossils -- Juvenile fiction; Friendship -- Juvenile fiction; World records -- Fiction; Fossils -- Fiction; Friendship -- Fiction